Antiviral Activity of Interferon Alpha-Inducible Protein 27 Against Hepatitis B Virus Gene Expression and Replication - Ullah, Hafiz; Sajid, Muhammad; Yan, Kun; Feng, Jiangpeng; He, Miao; Shereen, Muhammad Adnan; Li, Qiaohong; Xu, Tianmo; Hao, Ruidong; Guo, Deyin; Chen, Yu; Zhou, Limin; et al. (Frontiers in Microbiology, 2021)
Despite the availability of effective vaccines, hepatitis B virus (HBV) is still a major health issue, and approximately 350 million people have been chronically infected with HBV throughout the world. Interferons (IFNs) are the key molecules in the innate immune response that restrict several kinds of viral infections via the induction of hundreds of IFN-stimulated genes (ISGs). The objective of this study was to confirm the Interferon alpha-inducible protein 27 (IFI27) as an ISG that could inhibit HBV gene expression and DNA replication both in cell culture and in a mouse model. In human hepatoma cells, the IFI27 was highly induced by the stimulation of IFN-alpha (IFN-α) and it potentiated the anti-HBV activity. The overexpression of IFI27 inhibited while silencing of IFI27 enhanced the HBV replication in HepG2 cells. However, the knocking out of IFI27 in HepG2 cells robustly increases the formation of viral DNA, RNA and proteins. Detailed mechanistic analysis of the HBV genome showed that a sequence (nucleotide [nt] 1715 to 1815) of the EnhII/Cp promoter was solely responsible for viral inhibition. Similarly, the hydrodynamic injection of IFI27 expression constructs along with HBV genome into the mice resulted in a significant reduction in viral gene expression and DNA replication. In summary, our studies suggested that IFI27 contributed a vital role in HBV gene expression and replication and IFI27 may be a potential antiviral agent for the treatment of HBV.